Ten Years After the CFA Franc Devaluation : Progress Toward Regional Integration in the WAEMU - van den Boogaerde, P.; Tsangarides, Charalambos (Washington, D.C. : International Monetary Fund, 2005)
This paper takes stock of the achievements toward integration in the West African Economic and Monetary Union (WAEMU) 10 years after the 1994 devaluation of the CFA franc. It investigates the lessons learned and evaluates progress toward economic convergence, examines the evolution of trade and competitiveness, and points to ways to remove impediments to greater integration. The paper concludes that a continued political commitment will be needed to overcome the important dissimilarities between WAEMU member countries that have limited the degree of convergence achieved to date, and to advance toward a full-fledged economic union.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet